High-shock silicon accelerometer with an over-range stopper - Lee, Jae Min; Jang, Chang Uk; Choi, Chang Jun; Kwon, Ki Beom; Han, Jeong Sam; Kwon, Nam Yeol; Ko, Jong Soo (Journal of mechanical science and technology, 2016)
In this research, an accelerometer with an over-range stopper was designed, fabricated and evaluated. When a shock beyond the sensing range is applied to an acceleration sensor, an over-range stopper limits the amount of longitudinal deformation in the sensing bridge, which is weak to shocks, below a certain level and so prevents the acceleration sensor from breaking. To analyze the effect of the overrange stopper shape on acceleration sensor performance, we fabricated high-shock accelerometers with over-range stoppers of three different lengths (short, medium and long models). We then performed a comparative analysis of the performance of each accelerometer.